2015
DOI: 10.1521/jscp.2015.34.9.788
|View full text |Cite
|
Sign up to set email alerts
|

Mother and Father Attributions for Child Misbehavior: Relations to Child Internalizing and Externalizing Problems

Abstract: Knowledge of how parents think about their children's misbehavior is important in understanding the behavioral and emotional problems of children. Relations between parent attributions for child misbehavior and child functioning were examined in a community sample of 163 two-parent families of 9-12 year-old boys and girls. Mother and father attributions were assessed along child-responsible and parent-causal dimensions. Both parent-and child-reported internalizing and externalizing problems were measured. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Impact of parenting attributions on child behaviour. There is a well-established relationship between parental attributions and child behavioural problems (Colalillo, Miller, & Johnston, 2015;Johnston, Hommersen, & Seipp, 2009). Previous studies have shown that parents of typically developing children, tend to see child behavioural problems as external, variable and uncontrollable (Butcher & Niec, 2017) leading to calmer parenting responses and less perceived blame on the child.…”
Section: Relationship Between Parental Attributions and Child And Parmentioning
confidence: 99%
See 4 more Smart Citations
“…Impact of parenting attributions on child behaviour. There is a well-established relationship between parental attributions and child behavioural problems (Colalillo, Miller, & Johnston, 2015;Johnston, Hommersen, & Seipp, 2009). Previous studies have shown that parents of typically developing children, tend to see child behavioural problems as external, variable and uncontrollable (Butcher & Niec, 2017) leading to calmer parenting responses and less perceived blame on the child.…”
Section: Relationship Between Parental Attributions and Child And Parmentioning
confidence: 99%
“…On the contrary, parents of children with high levels of conduct problems tend to have more negative parental attributions, seeing the misbehaviour as internal, stable and controllable (Coles et al, 2010;Sawrikar & Dadds, 2018) leading to higher use of dysfunctional parenting responses. Colalillo et al (2015) examined a community sample of mothers and fathers and found that children of mothers who attributed responsibility to the child's misbehaviour, presented high levels of child externalising problems. Also, both maternal and paternal attributions predicted child internalising problems.…”
Section: Relationship Between Parental Attributions and Child And Parmentioning
confidence: 99%
See 3 more Smart Citations